2016
DOI: 10.1007/s11200-015-1278-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of prestack diffraction data and attributes using a traveltime decomposition approach

Abstract: Diffractions not only carry important information about small-scale subsurface structures, they also possess unique properties, which make them a powerful tool for seismic processing and imaging. Since a point diffractor scatters an incoming wave to all directions, a diffraction event implies better illumination than a reflection, because the rays travel through larger parts of the subsurface. Furthermore, unlike the reflection case, in which the emergence location of the reflected wave depends on the source p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…8, but it makes use of dynamic ray tracing to perform the subsequent projection into image space. Also, the method was shown to reliably utilize diffracted energy to arrive at a resolved estimate of scatterer locations in depth (Duveneck, 2004;Bauer et al, 2017). While the projection step, like in focusing, could be performed for a predefined velocity distribution, projection was shown to lend itself well to a largely automated reconstruction of not only the scatterer locations, but also the macro-velocity structure in an iterative process.…”
Section: Potential and Extension Of The Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8, but it makes use of dynamic ray tracing to perform the subsequent projection into image space. Also, the method was shown to reliably utilize diffracted energy to arrive at a resolved estimate of scatterer locations in depth (Duveneck, 2004;Bauer et al, 2017). While the projection step, like in focusing, could be performed for a predefined velocity distribution, projection was shown to lend itself well to a largely automated reconstruction of not only the scatterer locations, but also the macro-velocity structure in an iterative process.…”
Section: Potential and Extension Of The Methodsmentioning
confidence: 99%
“…Likewise applied before migration, there are some techniques that make direct use of wave-field coherence for diffraction separation (Berkovitch et al, 2009;Dell and Gajewski, 2011;Bauer et al, 2016;Bakhtiari Rad et al, 2018). While these methods specifically target the diffracted wave field for extraction, recent developments have shown that a more surgical, amplitude-preserving separation can be achieved by assessing the coherence of reflections instead (Schwarz and Gajewski, 2017a;Schwarz, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately linked to illumination, provided that the assumption of a point scatterer is reasonably justified at least for a subset of the considered wavefield, the recorded prestack diffraction response turns out to be highly symmetric and redundant (e.g. Bauer et al, 2016;Schwarz and Gajewski, 2017a).…”
Section: Symmetries and Correlationsmentioning
confidence: 99%
“…To illustrate the benefit of separating the full prestack diffraction response, we apply time migration velocity analysis to prestack diffraction-only data in order to obtain the required migration velocities for subsequent imaging in time. This paper only considers diffraction from point-like structures, as even more complicated diffractors such as edges or wedges, from a kinematic viewpoint, contain a non-Snell scattering component that provides increased illumination (Bauer et al, 2016(Bauer et al, , 2017. For this diffraction component, the estimated stacking velocities are intrinsically dip-independent and can readily be used for prestack or poststack time migration (see, e.g., Sava et al, 2005;Fomel et al, 2007;Berkovitch et al, 2009;Bakhtiari Rad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%